2001
DOI: 10.1007/s00268-001-0041-4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperamylasemia and subclinical pancreatitis after cardiac surgery

Abstract: Hyperamylasemia after cardiac surgery is common but typically causes no clinical concern because it consists mainly of the salivary isoenzyme. In this study we evaluated the incidence, source, and time course of postoperative hyperamylasemia with special attention to the possibility of subclinical pancreatitis. In 88 patients prospectively tested for serum amylase and lipase concentrations, elastase 1 activity, and amylase isoenzyme characteristics, 57 (64%) showed hyperamylasemia during the early postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…Several authors reported that hyperamylasemia during the early days after surgery was frequently of salivary origin. [21][22][23] In this study, serum total amylase levels were significantly higher than serum pancreatic amylase levels on POD 1, 2, 5, and 7, although no significant difference existed between drainage fluid total amylase levels and drainage fluid pancreatic amylase levels. Additionally, in 36% of the patients, the serum total amylase levels were more than three times the serum pancreatic amylase levels on POD 1.…”
Section: Discussionmentioning
confidence: 91%
“…Several authors reported that hyperamylasemia during the early days after surgery was frequently of salivary origin. [21][22][23] In this study, serum total amylase levels were significantly higher than serum pancreatic amylase levels on POD 1, 2, 5, and 7, although no significant difference existed between drainage fluid total amylase levels and drainage fluid pancreatic amylase levels. Additionally, in 36% of the patients, the serum total amylase levels were more than three times the serum pancreatic amylase levels on POD 1.…”
Section: Discussionmentioning
confidence: 91%
“…A decreased rate of excretion into urine, rather than pancreatic cellular damage, has been postulated as a major cause 29 . Late hyperamylasaemia may indicate subclinical pancreatitis 30 .…”
Section: Discussionmentioning
confidence: 99%
“…301,302 Isolated hyperamylasemia in the early postoperative period is usually not associated with clinical symptoms or an elevated lipase level, and most commonly arises from a nonpancreatic source, such as the salivary glands, or results from decreased renal excretion. Lactic acidosis may result from impaired lactate metabolism rather than lactate generation from impaired tissue perfusion.…”
Section: Treatmentmentioning
confidence: 99%
“…Lactic acidosis may result from impaired lactate metabolism rather than lactate generation from impaired tissue perfusion. 302 This is suggested by the presence of mild symptoms (anorexia, nausea, ileus) with elevation of serum lipase levels. K. Hyperamylasemia is noted in a substantial number (35-65%) of patients in the early postbypass period but is associated with clinical pancreatitis in only about 1-3% of patients.…”
Section: Treatmentmentioning
confidence: 99%